A randomized controlled pilot study of ulipristal acetate for abnormal bleeding among women using the 52‐mg levonorgestrel intrauterine system. Issue 1 (11th December 2019) - Fava, Mariana; Peloggia, Alessandra; Baccaro, Luiz F.; Castro, Sara; Carvalho, Nelsilene; Bahamondes, Luis
Abstract: Objective: To assess the efficacy of ulipristal acetate (UPA) for reducing abnormal bleeding among women using the 52‐mg levonorgestrel intrauterine system (LNG‐IUS). Methods: A randomized, double‐blind, placebo‐controlled pilot study conducted from September 1, 2016 to September 30, 2018, at the University of Campinas, Brazil. LNG‐IUS users reporting prolonged or frequent uterine bleeding for at least 1 year were randomized to receive 5 mg UPA per day for 5 days or placebo at an identical regimen. Bleeding was recorded for 90 days after treatment began and was compared between the groups. Results: Of 94 eligible women, 64 with abnormal bleeding associated with LNG‐IUS use declined treatment or device removal after counselling regarding anticipated bleeding patterns. For the 25 study participants, differences were nonsignificant between the UPA and placebo groups for number of days before bleeding stopped and days free of bleeding; however, UPA users displayed a trend for shorter duration before bleeding stopped and longer time free of bleeding. A similar trend for mean number of bleeding days at 30‐, 60‐, and 90‐day follow‐up was observed. Conclusion: A nonsignificant trend in reduction of abnormal bleeding was observed among LNG‐IUS users taking 5 mg UPA per day for 5 days compared with placebo; however, further research is needed. ClinicalTrials.gov: NCT03186586: Abstract : A nonsignificant trend in reduction of abnormal bleeding was observed among levonorgestrel intrauterine system users taking 5 mg ulipristal acetate per day for 5 days compared with placebo.